Green Synthesis of Copper Nanoparticles Using Red Dragon Fruit (Hylocereus polyrhizus) Extract and Its Antibacterial Activity for Liquid Disinfectant - Cindy Agriningsih Haruna; Widy Aprillia Malik; Muhammad Yaqub Syamsul Rijal; Abdul Haris Watoni; La Ode Ahmad Nur Ramadhan (Jurnal Kimia Sains dan Aplikasi, 2022)
The effort of copper nanoparticle exploration for antibacterial cleaning agents needs to prevent infection or contamination of microorganisms such as bacteria and viruses due to its potential characteristic as an environmentally benign material. The synthesis of copper nanoparticles using 0.02 M Cu(NO3)2 as a precursor and red dragon fruit extract as a bioreduction agent has been conducted. The extraction process of red dragon fruit was done by the maceration method using methanol as solvent. Copper nanoparticles were prepared through green chemistry with the reduction method. The compound in red dragon fruit extract reduced Cu2+ to Cu. The experimental nanoparticle synthesis method was performed with a combination of red dragon fruit extract and Cu(NO3)2 solution mixed with a volume ratio of bioreductor extract toward Cu2+ precursor variation of 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, and 1:9. The mixtures were stirred using a magnetic stirrer for 30 minutes and then incubated. The samples were characterized using UV-Vis (Ultraviolet-Visible), FTIR (Fourier Transform Infrared), and a digital microscope to observe morphology. The observation continued to assess its antibacterial activity and potency as an active disinfectant. UV-Vis analysis showed that the absorbance value for 30 minutes tended to be stable. Particle size estimation showed the smallest size of 122.12 nm at a volume ratio of 1:9. Functional group analysis using FTIR showed a shift in wavenumber between dragon fruit extract and copper nanoparticle (CuNPs), indicating a functional group interaction. The results of morphological analysis using a digital microscope showed that the particles with fine powder granules were produced with the composition of fruit extract: Cu(NO3)2 of 1:9. Antibacterial activity against Staphylococcus aureus and Escherichia coli indicated that the composition of Cu-nanoparticles of 1:9 had given an inhibition value.